Exploring the genomic diversity of potato virus Y and its interaction with hosts - MORAIS JÚNIOR, I. J. de (2024)
we initiated the analysis of PVY isolates collected from tomato (PVYSl), potato (PVYSt), and pepper (PVYCa) production fields. A genomic sequencing protocol was developed using Nanopore technology so we could simultaneously sequence the genomes of PVYCa, PVYSt, and PVYSl, significantly reducing operational costs. We also evaluated the resistance to PVY infection of tomato and pepper cultivars, and Solanum spp. lines from the Germplasm Bank of the Instituto Agronômico de Campinas. None of the evaluated tomato, pepper cultivars, and germplasm bank accessions showed resistance to PVY infection, indicating an urgent need to find materials with some level of resistance for the market and breeding programs.